Penerapan Teknik Participatory Rural Appraisal (Pra) Dalam Menangani Permasalahan Lingkungan di Desa Sukamaju Kabupaten Sukabumi - Aulia Putri; Elma Meidiana Rahmah; Hanny Rifanela; Nazla Bunga Qonita; Tawfiqurrohman Tawfiqurrohman (Jurnal Ilmiah Wahana Pendidikan, 2022)
The living environment should be the most comfortable place for eachindividual. But in fact there are several factors that can affect comfortness,one of which is environmental problems. To find causes and effects as wellas solutions to these problems, of course, requires direct participationfrom the community. The Participatory Rural Appraisal (PRA) techniquecan be an approach that can be used and open a discussion forum in thecommunity so that they can participate in voicing their opinions aboutproblems that exist in their living environment. Desa Sukamaju,Kecamatan Kadudampit, Kabupaten Sukabumi, Provinsi Jawa Barat waschosen as the location for researchers to carry out PRA activities. Theresearch method used in this research is qualitative action research. Fromthe results of the discussion forum held with the community, it was foundthat the waste problem was ranked first. This is concluded through thePRA technique of pohon masalah, matriks ranking, and pemetaan desa.For these problems, education about ecobricks and socialization on wastemanagement was held as a solution to the waste problem in DesaSukamaju.